CAMPUR KODE KATA DALAM NOVEL RADIKUS MAKAN KAKUS KARYA RADITYA DIKA - Sarujin (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This study aims to obtain a description of the type and form of code-mixing in the novel word Radikus Makankakus, works: Raditya Dika. The research data was sourced from the novel Radikus Makankakus, works: Raditya Dika. Collecting data in this study using basic techniques which refer to tangible tapping techniques and techniques recorded as engineering sequel. Based on the results of the research, that the novel Radikus MakanKakus, found mixed the type of code into the (inner code maxing) and mixed the type of code to the outside (outer code maxing). Mixed types of code into (innercode mixing) were found among other code-mixing into the (inner code maxing) tangible good word said base and said complex. In addition, also found mixed the type of code to the outside (outer code maxing). Mixed types of code to the outside (outer code maxing) found in novels include code-mixing outer tangible to both said basic words and complex words.